How depression and ADHD relate to exercise addiction: a cross-sectional study among frequent exercisers - Baltes-Flueckiger, Lavinia; Wagner, Aline; Sattler, Isabel; Meyer, Maximilian; Tschopp, Amos; Walter, Marc; Colledge, Flora (Frontiers in Psychology, 2024)
Background To date, there are no official diagnostic criteria for the frequently reported phenomenon of exercise addiction. Therefore, the aim of the present study was to investigate how mental disorders, specifically depression and attention-deficit hyperactivity disorder (ADHD), are related to exercise addiction (EA). Methods A total of 173 participants aged between 18 and 70 years, who reported exercising more than 10 h a week and continued to exercise despite injury or illness, answered questionnaires including the Exercise Dependence Scale, the Beck Depression Inventory, and the Homburger ADHD scale for adults. Multiple linear regression analyses were performed adjusting for relevant confounders (age, gender) and stepwise regression was used to identify which of the two mental disorders is the more influential predictor of EA. Results Pearson correlation analysis showed that depressive symptoms [r (171) = 0.422, p < 0.00] and ADHD symptoms [r (171) = 0.308, p < 0.001] were positively correlated with EA symptoms. The relation between depressive symptoms and EA remained after adjusting for confounders in the regression model (B = 20.531; t(170) = 5.950; 95% CI [13.719, 27.343]; p < 0.001). Similarly, the positive link between ADHD symptoms and EA persisted after controlling for confounders (B = 15.507; t(170) = 3.771; 95% CI [7.389, 23.625]; p < 0.001). Additionally, a stepwise regression model identified that depressive symptoms are a stronger predictor for EA than ADHD symptoms. Conclusion Depressive symptoms seem to be a stronger predictor for EA compared to ADHD symptoms in frequent exercisers. Although individuals with ADHD May exercise extensively, they might be less at risk for EA than individuals with depression. These results contribute to the complex characterization of the psychiatric profile of individuals with exercise addiction, and underline the need for further research elucidating the interplay between mental disorders and EA.